Corporate social responsibility internal as a predictor for motivation to serve, normative commitment, and adaptive performance among State-owned Enterprises' employee - Rudy M. Ramdhan; Alex Winarno; Daniel Kisahwan; Deni Hermana (Cogent Business & Management, 2022)
Very drastic environmental changes require the development of an adaptive performance management framework that supports the strengths of the company's structure. Proving the position of internal CSR as a resource that can solve performance problems needs to be done. This study aims to analyze the role of internal corporate social responsibility as a predictor of motivation to serve, normative commitment, and adaptive performance in Pandemic COVID 19 among State-owned enterprises Employees. The research design used causal studies to test the influence by using a survey of 289 employees holding State-owned Enterprises (SOEs) of the defense industry non-managers who were randomly selected. Findings of research show the motivation for high performance grows in line with the attention and support of the company at the time of pandemic with the existence of internal corporate social responsibility. Normative commitments increase and impact adaptive performance. Performance grows along with the activation of personal norms (moral responsibility) and the activity of individual values as employees in State-owned enterprises. The employees identify themselves as part of an organization that must devote itself to the interests of the state. Internal corporate social responsibility influences adaptive performance both directly and through motivation to serve and normative commitment. Theoretical implications are focused on developing ethical theories that underlie motivation to serve and normative commitments. Practical implications are focused on efforts to realize internal corporate social responsibility based on the foundation that is sourced on environmental ethical awareness. Originality is the contribution of expanding understanding of internal corporate social responsibility functions reviewed from the process to improve performance based on Self-determination theory and norm activation theory.
Keywords: 650; Corporate social responsibility internal; employee; motivation to serve; normative commitment; state-owned enterprises holding defense